Trapping and Cooling of Single Atoms in an Optical Microcavity by a Magic-Wavelength Dipole Trap - 李文芳 杜金锦 文瑞娟 李刚 张天才 (Chinese physics letters, 2015)
We present trapping and cooling of single cesium atoms inside a microcavity by means of an intracavity far-off- resonance trap （FORT）. By the ＇magic＇ wavelength FORT, we achieve state-insensitive single-atom trapping and cooling in a microeavity. The cavity transmission of the probe beam strongly coupled to single atoms enables us to continuously observe the intracavity atom trapping. The average atomic localization time inside the bright FORT is about 7ms by introducing cavity cooling with appropriate detuning. This experiment presents great potential in coherent state manipulation for strongly coupled atom photon systems in the context of cavity quantum electrodynamics.